2011
DOI: 10.1002/hbm.21232
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in topological organization of structural brain networks in healthy individuals

Abstract: The aim of this study was to examine structural brain networks using regional gray matter volume, as well as to investigate changes in small-world and modular organization with normal aging. We constructed structural brain networks composed of 90 regions in young, middle, and old age groups. We randomly selected 350 healthy subjects for each group from a Japanese magnetic resonance image database. Structural brain networks in three age groups showed economical small-world properties, providing high global and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
161
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 84 publications
34
161
2
Order By: Relevance
“…local clustering and global efficiency) over all age categories, in contrast with previous literature showing alterations in both structural (Dennis et al, 2013;Gong et al, 2009;Hagmann et al, 2010;Montembeault et al, 2012;Otte et al, 2015;Wu et al, 2012;Zhu et al, 2012) and functional brain networks across life-span (Achard and Bullmore, 2007;Betzel et al, 2014;Meier et al, 2012;Meunier et al, 2009;Nathan Spreng and Schacter, 2012;Simpson and Laurienti, 2015;Smit et al, 2016;Wang et al, 2012). Furthermore, our findings are also in contrast with significant differences found in a previous exponential random graph modeling study in functional networks , and a recently developed similar approach (also discussed below) which revealed differences in functional networks across the lifespan, such as older adults having stronger connections between highly clustered nodes, or less assortativity in visual and multisensory regions (Simpson and Laurienti, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…local clustering and global efficiency) over all age categories, in contrast with previous literature showing alterations in both structural (Dennis et al, 2013;Gong et al, 2009;Hagmann et al, 2010;Montembeault et al, 2012;Otte et al, 2015;Wu et al, 2012;Zhu et al, 2012) and functional brain networks across life-span (Achard and Bullmore, 2007;Betzel et al, 2014;Meier et al, 2012;Meunier et al, 2009;Nathan Spreng and Schacter, 2012;Simpson and Laurienti, 2015;Smit et al, 2016;Wang et al, 2012). Furthermore, our findings are also in contrast with significant differences found in a previous exponential random graph modeling study in functional networks , and a recently developed similar approach (also discussed below) which revealed differences in functional networks across the lifespan, such as older adults having stronger connections between highly clustered nodes, or less assortativity in visual and multisensory regions (Simpson and Laurienti, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have shown a higher local clustering and lower global efficiency in older adults compared to younger adults (Zhu et al, 2012), where modularity decreases across networks (Meunier et al, 2009). In line with these findings several studies have shown inverted-U shaped global efficiency across lifespan (Otte et al, 2015;Wu et al, 2012). Functional connectivity assessment has revealed increased integration and decreased randomness, whereas connectivity decreased significantly during adulthood (Smit et al, 2016).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Modular organization changes greatly in elderly people compared with the young and middleaged. The old showed a decrease in the connector ratio and inter-module connections [51] . In another study, older people showed a decrease in the inter-modular organization frontal and an increase in the posterior and central modules [35] .…”
Section: Normal Brain Network Organizationmentioning
confidence: 99%
“…As with global and regional measures of structural brain changes, structural covariance changes with age are more prominent between frontal brain and posterior cortices, reflecting a loss of long-range covariance in favor of increased local processing [61,63,64]. Another prominent feature of network-level changes is declining structural covariance within the default network, a collection of functionally-connected brain regions implicated in mnemonic and associative processing [65].…”
Section: Changes In Structural Brain Networkmentioning
confidence: 99%